Green development environment and sustainability in a developing world - Adams, W. M. (William Mark) 1955- (Routledge, Taylor & Francis Group, 2020)
"In print continuously since 1990, Green Development has won a place as a leading account of sustainable development used by generations of undergraduate and graduate students. This authoritative and readable text provides a clear and coherent analysis of sustainable development in theory and practice. The fourth edition of Green Development is fully revised, and up to date. It offers clear insights into the challenges of environmental sustain- ability, and social and economic development. The book has proved its value to generations of students as an authoritative, thought-provoking and readable guide to the field of sustainable development"--